Student Facilitated PBL – A Capstone Collaborative Learning Experience in the Griffith University MBBS Program. - Alexander, Heather; Tedman, Raymond; Wallace, Barbara; Pountney, Helen (International Journal of Emerging Technologies in Learning (iJET), 2011)
We report on an innovation in teaching and learning designed to extend the collaborative learning of PBL, that occurs during the first two years of a four year graduate entry medical program, to a capstone learning experience to assist the transition to a hospital based year 3. During the last five weeks of Year 2 the PBL sessions consist of an initial student facilitated session early in the week followed by a large format session for the entire class convened by two clinicians. The new format PBL was perceived positively by the students and staff involved and may have advantages over traditional formats in developing studentsâ?? clinical reasoning and differential diagnosis skills.